Small and low-cost AVG for distributed production lines and warehouses - António Paulo Moreira (2008)
Consumer's standards are getting higher, and the global market is morecompetitive than ever, demanding much more from the industry and services. Thus,material resources management is crucial to every company. The transport of materialsbetween a warehouse and a production line is one classic example of a process possible tobe optimized. The aim of this paper is to present the development of a prototype for anAutomated Guided Vehicle, AGV. The purpose of the work was to build a small, lowcost,and electric vehicle able to transport small packages. All control devices,supervision applications, and user-interface software, was entirely developed for thisproject. Furthermore, the behavior of the robot will also be analyzed and discussed in thisarticle.